Fault-Tolerant Control of Multi-UAV Attitude Based on Predictive Control in Uncertain Network Environment - Jiacheng Bin; Fang Liu; Qingnan Huang; Qiqi Wu; Xianming Xie (IEEE Access)
This paper analyzes the simultaneous occurrence of actuator faults (AF) and sensor faults (SF) in a Multi-Unmanned Aerial Vehicle (UAV) system operating in an unreliable network environment, and designs a distributed fault-tolerant control (FTC) scheme based on predictive control theory. First, the existence of Markov-based uncertain time delay in the system is considered, and generalized to obtain a Markov Jump System (MJS). Secondly, after analyzing the system with input constraints, sufficient conditions for stochastically stabilizing the augmented system are derived using the Lyapunov function; then, the matrix to be solved is computed after decoupling the sufficient conditions; Finally, the effectiveness of the proposed method is demonstrated through numerical simulations.